Evaluation of diflubenzuron–verapamil combination strategy for eco-safe management of Aedes aegypti - Sankar, Manu; Yadav, Divya; Kumar, Sarita (Frontiers in Physiology, 2024)
IntroductionAedes aegypti, the vector of multiple arboviral diseases, is a prime health concern worldwide. The surge in Aedes-borne diseases emphasizes the urgent need for efficient vector control measures. Synthetic pesticides used traditionally, however, present environmental concerns and issues like resistance development, causing the use of higher chemical doses. Hence, alternate interventions like the use of insect growth regulators (diflubenzuron; DFB) show promise because of their unique mechanism of action and environmental safety. Nevertheless, mosquitoes have the potential to develop resistance to any chemical. Thus, the present study investigates the use of DFB in combination with verapamil (DFB-V; 1:10) as a possible mosquito intervention measure.MethodsThe effects of both DFB and DFB-V were assessed on the larval development, adult emergence and expression of detoxification enzymes, non-specific esterases, glutathione S-transferase (GST), acetylcholinesterase (AChE), and monooxygenases in laboratory-reared (AND-Ae. aegypti) and wild-caught (GVD-Ae. aegypti) strains of Ae. aegypti. The effects on the survival of non-target organisms were also investigated. ResultsThe investigations showed that DFB-V treatment of the Ae. aegypti fourth instars caused a 1.16–1.37 fold higher adult emergence suppression than DFB alone, reducing the IE50 values. The DFB treatment increased β-esterases, AChE, and monooxygenases but reduced the GST and α-esterase levels. The effects enhanced with the use of DFB-V, causing a significant decrease in α-esterase (7.7-fold) and an increase in monooxygenases (7.8-fold) (p < 0.05) in AND-Ae. aegypti compared to the wild-caught strain. The variation in enzyme levels in the two strains may be due to the stress caused by insecticides of different chemical natures used in the fields. No negative effects were observed on the non-target organisms—Gambusia affinis, Mesocyclops thermocyclopoides, and Paramecium tetraurelia.ConclusionThe studies showed the growth regulatory efficacy of DFB and probable role of GST and α-esterases in increasing the effects of DFB when synergized with verapamil. Further, the DFB-V combination did not result in any significant negative effects on the non-target organisms ascertaining its safe use. This is the first report unraveling the effects of the DFB–verapamil combination on the defense mechanism of Ae. aegypti. Further studies may assist in developing focused and eco-safe plans for managing Ae. aegypti populations effectively.